Spatially explicit paleogenomic simulations support cohabitation with limited admixture between Bronze Age Central European populations - Jérémy Rio (Nature Portfolio, 2021)
Rio et al. design and utilise spatially explicit simulations of genomic components to investigate the cohabitation or competition hypothesis of Bronze Age Central European human populations. Their results support cohabitation with limited gene flow between pastoralists and farmers, linking together palaeogenomic and archaeological observations from the literature.